2010
DOI: 10.1308/003588410x12699663904312
|View full text |Cite
|
Sign up to set email alerts
|

Early complications of total hip and knee replacement: a comparison of outcomes in a regional orthopaedic hospital and two independent treatment centres

Abstract: INTRODUCTION There is anecdotal evidence of poorer outcomes from prosthetic joint replacement performed in independent treatment centres but very few comparative studies. PATIENTS AND METHODS We compared the early re-operation, dislocation, re-admission, major wound infection and audit rates of 880 total hip (THA) and 874 total knee (TKA) arthroplasties carried out at a regional orthopaedic hospital (Avon Orthopaedic Centre; AOC) with 368 THAs and 365 TKAs from an NHS (WGH) and 67 THAs and 86 TKAs from a priva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…Prosthetic hip dislocation occurs in 1-10% of patients after total hip arthroplasty. 1 About 7000 primary hip joint replacements and 100 revisions are carried out annually in New Zealand. 2 The majority of primary dislocations are posterior and occur within the first three postoperative months.…”
Section: Introductionmentioning
confidence: 99%
“…Prosthetic hip dislocation occurs in 1-10% of patients after total hip arthroplasty. 1 About 7000 primary hip joint replacements and 100 revisions are carried out annually in New Zealand. 2 The majority of primary dislocations are posterior and occur within the first three postoperative months.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Bannister et al compared the outcomes for total replacement of the hip and knee carried out in a local AHT compared with two regional ISTCs. 8 They reported considerable variation in outcome, with a marked increase in the prevalence of reoperation and wound complications, as well as a trend towards a higher prevalence of hospital readmission for arthroplasty, carried out at ISTCs. The findings from the present study enable an informed opinion with regard the stated aims of ISTCs.…”
Section: Discussionmentioning
confidence: 99%
“…Further information is also taken from a comprehensive report on ISTCs from the House of Commons (HoC). 8 With regard to increasing elective capacity available to the NHS to reduce waiting lists and waiting times, evidence from the HoC Health Committee Report 1 stated that ISTCs provided only a modest increase in capacity. This report detailed that, as of December 2005, ISTCs had carried out 44,000 elective surgical procedures and 9,000 diagnostic procedures, with phase-I centres expected to carry out a mean of 170,000 Finished Consultant Episodes (FCEs) each year over 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Kreder et al [20] reported that a low hospital procedure volume was significantly associated with an increased rate of readmission within one year after TKA, and low surgeon volume was related to a longer hospital stay. In addition, Bannister et al [21] reported that the number of major wound infections at hospitals with few joint replacements was 17 times greater than that at the hospitals with many joint replacements. Ong et al [22] reported that patients who underwent TKA at high-volume hospitals or by high-volume surgeons are more likely to undergo shorter operative procedures than those operated at low-volume hospitals or by lowvolume surgeons.…”
Section: Variablementioning
confidence: 99%